Pseudomonas aeruginosa: A typical biofilm forming pathogen and an emerging but underestimated pathogen in food processing - Li, Xuejie; Gu, Nixuan; Huang, Teng Yi; Zhong, Feifeng; Peng, Gongyong (Frontiers in Microbiology, 2023)
Abstract: Pseudomonas aeruginosa (P. aeruginosa) is a notorious gram-negative pathogenic microorganism, because of several virulence factors, biofilm forming capability, as well as antimicrobial resistance. In addition, the appearance of antibiotic-resistant strains resulting from the misuse and overuse of antibiotics increases morbidity and mortality in immunocompromised patients. However, it has been underestimated as a foodborne pathogen in various food groups for instance water, milk, meat, fruits and vegetables. Chemical preservatives that are commonly used to suppress the growth of food source microorganisms can cause problems with food safety. For these reasons, finding effective, healthy safer, and natural alternative antimicrobial agents used in food processing is extremely important. In this review, our ultimate goal is to cover recent advances in food safety related to P. aeruginosa including antimicrobial resistance, major virulence factors, and prevention measures. It is worth noting that food spoilage caused by P. aeruginosa should arouse wide concerns of consumers and food supervision department.